2011
DOI: 10.1002/mus.21946
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol‐related peripheral neuropathy: Nutritional, toxic, or both?

Abstract: Alcohol-related peripheral neuropathy (ALN) is a potentially debilitating complication of alcoholism that results in sensory, motor, and autonomic dysfunction. Unfortunately, ALN is rarely discussed as a specific disease entity in textbooks because it is widely assumed to primarily reflect consequences of nutritional deficiency. This hypothesis is largely based on observations first made over eight decades ago when it was demonstrated that thiamine deficiency (beriberi) neuropathy was clinically similar to ALN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 53 publications
1
67
0
8
Order By: Relevance
“…[ Studies by Ammandola et al [12] and Mellion et al [18] established significant association between duration of alcohol consumption and cumulative alcohol intake (TLDE) to neuropathy. In the present study, the average duration of alcohol consumption was 17.3 ± 6.6 years.…”
Section: Discussionmentioning
confidence: 99%
“…[ Studies by Ammandola et al [12] and Mellion et al [18] established significant association between duration of alcohol consumption and cumulative alcohol intake (TLDE) to neuropathy. In the present study, the average duration of alcohol consumption was 17.3 ± 6.6 years.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin B12 deficiency can result in paresthesia, peripheral neuropathy, and demyelination of the corticospinal tract and dorsal columns (Robert and Brown, 2003). The possibility of alcoholic sensory neuropathy was considered as chronic ethanol exposure can cause polyneuropathy characterized by axonal degeneration (Mellion et al, 2011). Recent studies have shown that ethanol exposure has direct neurotoxic effects on peripheral nerves.…”
Section: Paraesthesiamentioning
confidence: 99%
“…In recent years the social habits in the western world have changed and food additives may ameliorate the most severe damage. Whether the neuropathy is primarily due to the effect of alcohol, or if it is secondary to nutritional defects accompanying alcoholism has been a source of discussion for a long time [1][2][3][4][5][6][7][8][9][10]. Since some patients with chronic alcoholism and neuropathy do not have a clear nutritional deficiency, and as the neuropathy often does not respond to pure nutritional supplementation, it has become clear that there is also a direct toxic effect of alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…alcohol related peripheral neuropathy epidemiology The term alcohol-related peripheral neuropathy (ALN) [9] is useful epidemiologically, as it combines both alcohol and neuropathy. The estimated prevalence of neuropathy in patients who suffer from alcoholism, as defined by DSM IV criteria, is between 25 and 66 % in the American population [4,11].…”
Section: Introductionmentioning
confidence: 99%